2023
DOI: 10.1007/s11060-022-04203-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, predictors and prognostic relevance of high-grade hematotoxicity after temozolomide or temozolomide-lomustine in the CeTeG/NOA-09 trial

Abstract: Purpose In the randomized phase III trial CeTeG/NOA-09, temozolomide (TMZ)/lomustine (CCNU) combination therapy was superior to TMZ in newly diagnosed MGMT methylated glioblastoma, albeit reporting more frequent hematotoxicity. Here, we analyze high grade hematotoxicity and its prognostic relevance in the trial population. Methods Descriptive and comparative analysis of hematotoxicity adverse events ≥ grade 3 (HAE) according to the Common Terminology of Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are many proposed mechanisms for this resistance, however, currently the only reliable predictor is the methylation state of O 6 -methylguanine DNA methyltransferase (MGMT) promoter [ 93 ]. It should be emphasized that the recent CeTeG/NOA-09 trial suggests that TMZ and lomustine (also known as CCNU) can be an alternative option for newly diagnosed MGMT methylated GBM for young patients [ 94 ]. Even though the most recent Classification of the Tumors of the CNS by WHO in 2021 combined histopathological features with molecular markers [ 8 ] and significantly improved our understanding of these neoplasms, it did not translate to a major improvement in patient stratification according to their TMZ response [ 89 ].…”
Section: Chemotherapymentioning
confidence: 99%
“…There are many proposed mechanisms for this resistance, however, currently the only reliable predictor is the methylation state of O 6 -methylguanine DNA methyltransferase (MGMT) promoter [ 93 ]. It should be emphasized that the recent CeTeG/NOA-09 trial suggests that TMZ and lomustine (also known as CCNU) can be an alternative option for newly diagnosed MGMT methylated GBM for young patients [ 94 ]. Even though the most recent Classification of the Tumors of the CNS by WHO in 2021 combined histopathological features with molecular markers [ 8 ] and significantly improved our understanding of these neoplasms, it did not translate to a major improvement in patient stratification according to their TMZ response [ 89 ].…”
Section: Chemotherapymentioning
confidence: 99%
“…In the study by Weller et al, they found a non-significant increase in the incidence of grade ≥ 3 hematologic toxicity when temozolomide was combined with lomustine compared to temozolomide alone. The rates of hematologic toxicity were 36% and 29%, respectively [ 34 ]. Toxicity was predominantly observed in patients undergoing concurrent chemoradiotherapy.…”
Section: Reviewmentioning
confidence: 99%